Materials and preparation methods for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value
By designing a concrete material based on pH value unidirectional regulation, using nanoscale nesting effect and dehydration polymerization technology, the existing overall hydrophobic concrete has been solved in terms of strength and durability, and the conversion of concrete from hydrophilic to hydrophobic is realized, improving its density and permeability.
Patent Information
- Application Number
- CN202510026795.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-08
AI Technical Summary
After the existing integral hydrophobic concrete is incorporated with a hydrophobic agent, the concrete is insufficiently hydrated in the early stage, the strength is reduced, and the hydrophobic modifier is difficult to disperse evenly, resulting in the problems of weak hydrophobic areas and insufficient durability.
By designing a concrete material based on pH value unidirectional regulation, the dehydration and polymerization of aminopropyl trimethoxysilane and n-dodecyl trimethoxysilane on the surface of hydrophilic vapor phase nanosilica powder is formed to transform from hydrophilic to hydrophobic under a strong alkali environment, achieving uniform dispersion and strength improvement of the material.
This material promotes hydration reaction in the early stage of concrete hardening, enhances compactness, and transforms into hydrophobicity due to the alkaline environment in the later stage of hardening, effectively resisting the invasion of external moisture and corrosive ions, and improving the durability and hydrophobic properties of concrete.
Smart Images

Figure CN119461947B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a material for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value and a preparation method thereof. Background Art
[0002] Concrete is widely used in the construction industry due to its good mechanical properties and low cost. However, the hydrophilicity of concrete itself seriously affects the performance of its structure. In the early stages of concrete pouring and hardening, the pH value of concrete is low and its hydrophilicity is necessary. This is because the hydration reaction of concrete requires the participation of water to combine cement particles to form a hard structure. Therefore, at this stage, maintaining sufficient moisture inside the concrete is crucial to ensure that the concrete can fully harden and reach the desired strength. However, after the concrete structure is put into use, the pH value of the concrete will be higher and the concrete should have a certain degree of hydrophobicity. The reason is that too much water infiltrating into the concrete can cause problems such as steel corrosion, freeze-thaw damage, and other chemical attacks.
[0003] In order to solve the problem of reduced strength and insufficient durability caused by hydrophilicity of concrete after it is put into use, the existing technology mainly develops integral hydrophobic concrete by adding hydrophobic agents. This kind of concrete is not limited by the penetration depth, but also ensures the service life of the hydrophobic material and enhances its hydrophobic ability. However, there are still many problems with integral hydrophobic concrete in the existing technology: 1) The addition of hydrophobic materials will reduce the hydrophilicity of concrete in the early stage of coagulation and hardening, hinder the reaction between cementitious material particles and water, resulting in insufficient hydration of concrete in the early stage and reducing its strength; 2) Due to its agglomeration, the internally added hydrophobic material is difficult to be evenly dispersed in the cement-based material, resulting in large differences in hydrophobicity in different parts and forming obvious hydrophobic weak areas; 3) The activity or effectiveness of the internally added hydrophobic material weakens over time, and it is impossible to ensure that the concrete is in a completely hydrophobic state in the later stage of hardening, which affects the durability of the concrete. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a material and a preparation method for unidirectionally regulating the hydrophilic to hydrophobic conversion of concrete based on pH value, which not only promotes the hydration reaction of concrete cementitious materials in the early stage of hardening and enhances the density of the concrete structure, but also utilizes the strong alkaline environment inside the concrete to achieve the conversion from hydrophilic to hydrophobic, effectively resists the invasion of external moisture and corrosive ion media after the concrete hardens, and improves the durability of the concrete.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] A material for unidirectionally regulating the hydrophilic to hydrophobic properties of concrete based on pH value, comprising the following raw materials by weight percentage: 7% to 12% inorganic filler, 0.40% to 1.20% azobisisobutyronitrile, 5% to 10% aminopropyltrimethoxysilane, 0.20% to 1.00% dibutyltin dilaurate, 7% to 11% hydrophobic modifier, 14% to 19% anhydrous ethanol, 14% to 20% acid solution, 13% to 18% alkaline solution, and 20% to 24% deionized water.
[0007] Preferably, the inorganic filler is hydrophilic fumed nano-silica or inorganic particulate material, wherein the inorganic particulate material is composed of one of nano-scale or micron-scale diatomaceous earth, zinc oxide, nano-titanium dioxide, nano-clay, carbon-based nano-material or solid waste inorganic material.
[0008] Preferably, the hydrophobic modifier is selected from one of n-dodecyltrimethoxysilane or long carbon chain hexadecyltrimethoxysilane and n-octadecyltriethoxysilane.
[0009] The present invention also provides a method for preparing the material for unidirectionally regulating the conversion of concrete hydrophilicity to hydrophobicity based on pH value, comprising the following steps:
[0010] Step S1, weighing hydrophilic fumed nano-silica, aminopropyltrimethylsilane and n-dodecyltrimethoxysilane according to the weight percentage of the raw materials for later use;
[0011] Step S2, adding aminopropyltrimethylsilane to a beaker containing anhydrous ethanol, and heating in a water bath to obtain a composite solution A;
[0012] Step S3, under the same reaction conditions as step S2, adding hydrophilic fumed nano-silica to the composite solution A, adding azobisisobutyronitrile, continuing to stir to obtain a suspension solution B, filtering through a nanofiltration membrane to obtain a nano-silica wet body C, and washing, drying, grinding, and sieving to obtain a nano-silica powder D;
[0013] Step S4, adding n-dodecyltrimethoxysilane to another beaker containing anhydrous ethanol, heating in a water bath, and stirring to obtain a composite solution E;
[0014] Step S5, under the same reaction conditions as step S4, dibutyltin dilaurate and the obtained nano-silica powder D are added to the composite solution E, and the suspension solution F is obtained by continuous stirring, and the suspension solution F is filtered through a nanofiltration membrane to obtain a nano-silica wet body G, and the nano-silica powder H is obtained by washing, drying, grinding, and sieving;
[0015] Step S6, adding the obtained nano-silicon dioxide powder H into a beaker containing an acid solution, stirring and filtering, washing and drying, grinding and sieving at room temperature, to obtain a material for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value.
[0016] Preferably, in step S3, the preparation process of nano-silica powder D is: the obtained nano-silica wet body C is washed alternately with anhydrous ethanol and deionized water three times, and stored at room temperature for 2 hours, and then placed in a drying oven at 80°C for 8 hours. After drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain nano-silica powder D.
[0017] Preferably, in step S4, the preparation process of the composite solution E is: heating the beaker containing anhydrous ethanol and n-dodecyltrimethoxysilane in a water bath at a temperature of 50°C to 60°C, and stirring at a speed range of 500r / min to 800r / min to obtain the composite solution E.
[0018] Preferably, in step S5, the preparation process of the nano-silica powder H is: the obtained nano-silica wet body G is washed twice with anhydrous ethanol and deionized water alternately, and stored at room temperature for 2 hours, and then placed in a drying oven at 80°C for 8 hours. After drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain the nano-silica powder H.
[0019] Preferably, in step S6, the preparation process of the material for unidirectionally regulating the conversion of hydrophilic to hydrophobic concrete based on pH value is as follows: placing the obtained nano-silicon dioxide powder H in a beaker filled with an acid solution, stirring for 1 min at room temperature and filtering, then washing twice with anhydrous ethanol and deionized water, and then placing it in a drying oven at 80°C for 3 h. After drying, cooling and grinding are performed, and the material is sieved through an 800-mesh sieve to obtain the material for unidirectionally regulating the conversion of hydrophilic to hydrophobic concrete based on pH value, and then treated with an alkali solution before adding it to concrete.
[0020] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0021] The material for unidirectionally regulating the conversion of hydrophilic to hydrophobic concrete based on pH value provided by the present invention is an internally mixed concrete hydrophobic material, which uses the pH value of concrete at different stages to convert the material from hydrophilic to hydrophobic inside the concrete, and can dissolve in a hydrophilic form in a neutral solution, and evenly disperse in the concrete during the stirring process, promote hydration reaction, and convert into hydrophobicity due to the alkaline environment in which the concrete is located after hardening. In addition, the material makes full use of the nesting effect of the nanoscale and is firmly embedded in the concrete, thereby reducing the porosity and self-shrinkage performance of the concrete, improving its density, and effectively inhibiting the generation of shrinkage cracks, providing new ideas and methods for improving the performance of concrete, and helping to promote the progress and development of the building materials industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0023] Figure 1 The present invention is a flow chart of a method for preparing a material for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In order to make the objects, features and advantages of the present invention more clearly understood, the present invention is described in detail below.
[0026] like Figure 1 As shown, the present invention provides a method for preparing a material for unidirectionally regulating the conversion of concrete hydrophilicity to hydrophobicity based on pH value, comprising the following steps:
[0027] Step S1, weighing hydrophilic fumed nano-silica, aminopropyltrimethylsilane and n-dodecyltrimethoxysilane according to the weight percentage of the raw materials for later use;
[0028] Step S2, adding aminopropyltrimethylsilane to a beaker containing anhydrous ethanol, and heating in a water bath to obtain a composite solution A;
[0029] Step S3, under the same reaction conditions as step S2, adding hydrophilic fumed nano-silica to the composite solution A, adding azobisisobutyronitrile, continuing to stir to obtain a suspension solution B, filtering through a nanofiltration membrane to obtain a nano-silica wet body C, and washing, drying, grinding, and sieving to obtain a nano-silica powder D;
[0030] Step S4, adding n-dodecyltrimethoxysilane to another beaker containing anhydrous ethanol, heating in a water bath, and stirring to obtain a composite solution E;
[0031] Step S5, under the same reaction conditions as step S4, dibutyltin dilaurate and the obtained nano-silica powder D are added to the composite solution E, and the suspension solution F is obtained by continuous stirring, and the suspension solution F is filtered through a nanofiltration membrane to obtain a nano-silica wet body G, and the nano-silica powder H is obtained by washing, drying, grinding, and sieving;
[0032] Step S6, adding the obtained nano-silicon dioxide powder H into a beaker containing an acid solution, stirring and filtering, washing and drying, grinding and sieving at room temperature, to obtain a material for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value.
[0033] In step S1, the material is composed of the following raw materials by weight percentage: 7%~12% hydrophilic fumed nano-silica, 0.40%~1.20% azobisisobutyronitrile, 5%~10% aminopropyltrimethoxysilane, 0.20%~1.00% dibutyltin dilaurate, 7%~11% n-dodecyltrimethoxysilane, 14%~19% anhydrous ethanol, 14%~20% acid solution, 13%~18% alkaline solution, and 20%~24% deionized water.
[0034] Among them, hydrophilic fumed nano-silica as an inorganic filler can also be replaced by inorganic particle materials (nano- or micro-scale inorganic materials), wherein the inorganic particle materials include diatomaceous earth, zinc oxide, nano-titanium dioxide, nano-clay, carbon-based nano-materials (such as graphene or carbon nanotubes, etc.) or one of solid waste inorganic materials. n-Dodecyltrimethoxysilane as a hydrophobic modifier can also be replaced by long carbon chain hexadecyltrimethyloxysilane and n-octadecyltriethoxysilane.
[0035] In step S3, the preparation process of nano-silica powder D is as follows: the obtained nano-silica wet body C is washed alternately with anhydrous ethanol and deionized water three times, and stored at room temperature for 2 hours, and then placed in a drying oven at 80°C for 8 hours, and after drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain nano-silica powder D. In step S4, the preparation process of composite solution E is as follows: a beaker containing anhydrous ethanol and n-dodecyltrimethoxysilane is heated in a water bath at a temperature of 50°C to 60°C, and stirred at a speed range of 500r / min to 800r / min to obtain composite solution E. In step S5, the preparation process of nano-silica powder H is as follows: the obtained nano-silica wet body G is washed alternately with anhydrous ethanol and deionized water twice, and stored at room temperature for 2 hours, and then placed in a drying oven at 80°C for 8 hours, and after drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain nano-silica powder H. In step S6, the preparation process of the material for unidirectionally regulating the hydrophilic to hydrophobic conversion of concrete based on pH value is as follows: the obtained nano-silica powder H is placed in a beaker filled with an acid solution, stirred at room temperature for 1 minute and then filtered, then washed twice with anhydrous ethanol and deionized water, and then placed in a drying oven at 80°C for 3 hours. After drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain the material for unidirectionally regulating the hydrophilic to hydrophobic conversion of concrete based on pH value, and then treated with an alkaline solution before adding it to concrete.
[0036] According to the above content, the material uses aminopropyltrimethyloxysilane and n-dodecyltrimethyloxysilane to dehydrate and polymerize on the surface of hydrophilic gas-phase nano-silica powder, forming a transition from hydrophilic to hydrophobic in a strong alkaline environment. The material uses the water required for concrete mixing as a carrier to evenly disperse it into the concrete. The hydrophilic groups in the early stage of the material ensure the hydrophilicity of the concrete in the early stage of hardening, promote the degree of concrete hydration, and can also use the alkaline environment inside the concrete in the later stage to play a hydrophobic protective role; in addition, due to its nanoscale mosaic effect, the porosity of the concrete is reduced, thereby improving the strength and impermeability of the concrete. At the same time, the material can achieve dual-stage performance optimization mainly due to its unique physical and chemical properties: 1) The material exhibits good hydrophilicity in the hydration stage, can form a strong interaction with water molecules, and promote the hydration reaction of the cementitious material. 2) As the concrete solidifies and hardens, in a strong alkaline environment, the deprotonation ability of the functional groups on the surface of the nanoparticles is enhanced, and the concrete gradually changes to a hydrophobic state, forming a protective barrier to effectively block the intrusion of external moisture. 3) The material has a nano-level particle size and can be tightly and evenly filled in the microscopic pores of concrete, reducing the porosity of concrete and improving the mechanical properties and impermeability of concrete.
[0037] The present invention will be further described below through specific implementation methods.
[0038] Example 1
[0039] The raw materials used in this embodiment are composed of the following raw materials by weight percentage: 7% hydrophilic fumed nano-silica, 0.8% azobisisobutyronitrile, 8% aminopropyltrimethoxysilane, 0.2% dibutyltin dilaurate, 10% n-dodecyltrimethoxysilane, 17% anhydrous ethanol, 22% deionized water, 17% acid solution, and 18% alkaline solution. The acid solution is a 0.01 mol / L hydrochloric acid solution, the alkaline solution is a 0.1 mol / L sodium hydroxide solution, and the purity of the anhydrous ethanol is 99.7%.
[0040] According to the above raw material composition, the preparation method of the material includes:
[0041] (1) Weigh the raw materials in proportion and set aside;
[0042] (2) Add aminopropyltrimethyloxysilane to a beaker containing an appropriate amount of anhydrous ethanol, then transfer it to a water bath heating pot, control the temperature at 50-60°C, magnetic stirring speed at 700 r / min, and stir for 10 min to obtain composite solution A;
[0043] (3) Without changing the reaction temperature and stirring speed of step (2), a certain amount of hydrophilic fumed nano-silica and a small amount of azobisisobutyronitrile are added to the composite solution A, and stirring is continued for 2 hours to obtain a suspension solution B;
[0044] (4) Filter the suspension solution B with a nanofiltration membrane to obtain a nanosilica wet body C, and wash it with anhydrous ethanol and deionized water alternately for 3 times, then store it at room temperature for 2 hours, and then dry it in a drying oven at 80°C for 8 hours. After cooling, grind it and pass it through an 800-mesh sieve to obtain a nanosilica powder D;
[0045] (5) Add n-dodecyltrimethyloxysilane to a beaker containing an appropriate amount of anhydrous ethanol, then transfer it to a water bath heating pot, control the temperature at 60-70°C, and stir at a magnetic stirring speed of 800 r / min for 20 min to obtain a composite solution E;
[0046] (6) Without changing the reaction temperature and stirring speed of step (5), a certain amount of nano-silica powder D and a small amount of dibutyltin dilaurate are added to the composite solution E, and stirring is continued for 4 hours to obtain a suspension solution F;
[0047] (7) The suspension solution F is filtered through a nanofiltration membrane to obtain a nano-silica wet body G, which is then washed twice with anhydrous ethanol and deionized water alternately, stored at room temperature for 2 hours, and then dried in a drying oven at 80°C for 8 hours. After cooling, it is ground and passed through an 800-mesh sieve to obtain a nano-silica powder H;
[0048] (8) The obtained nano-silica powder H was placed in a beaker containing an acid solution, stirred at room temperature for 1 min, and then filtered. It was then washed twice with anhydrous ethanol and deionized water, and then placed in a drying oven at 80°C for 3 h. After drying, it was cooled and ground, and passed through an 800-mesh sieve to obtain a material that can unidirectionally regulate the hydrophilicity of concrete to hydrophobicity based on pH value, and then treated with an alkaline solution before being added to concrete.
[0049] In order to verify that the material of this embodiment based on pH value unidirectional regulation of concrete hydrophilic to hydrophobic has good performance, the material obtained in this embodiment is added to water, and then added to the mixing equipment together with cement, sand and gravel for mixing. The amount of the hydrophobic material is 0.3% of the cement amount, and the obtained concrete is tested for performance, wherein the test experiments include compression test, water absorption test and drop contact angle test. Among them, the experiment takes C40 concrete as the object, the cement uses PO42.5 ordinary silicate cement, the sand uses medium sand with a fineness modulus of 2.7, and the gravel uses 5mm~25mm continuous graded crushed stone.
[0050] Example 2
[0051] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 8% hydrophilic fumed nano-silica, 0.5% azobisisobutyronitrile, 10% aminopropyltrimethoxysilane, 0.5% dibutyltin dilaurate, 11% n-dodecyltrimethoxysilane, 15% anhydrous ethanol, 23% deionized water, 16% acid solution, and 16% alkaline solution.
[0052] Example 3
[0053] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 9% hydrophilic fumed nano-silica, 0.6% azobisisobutyronitrile, 8% aminopropyltrimethoxysilane, 0.4% dibutyltin dilaurate, 8% n-dodecyltrimethoxysilane, 18% anhydrous ethanol, 22% deionized water, 16% acid solution, and 18% alkaline solution.
[0054] Example 4
[0055] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 7% hydrophilic fumed nano-silica, 0.8% azobisisobutyronitrile, 8% aminopropyltrimethoxysilane, 0.2% dibutyltin dilaurate, 10% n-dodecyltrimethoxysilane, 17% anhydrous ethanol, 22% deionized water, 17% acid solution, and 18% alkaline solution.
[0056] The performance test process is the same as that of Example 1, but the amount of the hydrophobic material added is 0.8% of the cement content.
[0057] Example 5
[0058] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 8% hydrophilic fumed nano-silica, 0.5% azobisisobutyronitrile, 10% aminopropyltrimethoxysilane, 0.5% dibutyltin dilaurate, 11% n-dodecyltrimethoxysilane, 15% anhydrous ethanol, 23% deionized water, 16% acid solution, and 16% alkaline solution.
[0059] The performance test process is the same as that of Example 1, but the amount of the hydrophobic material added is 0.8% of the cement content.
[0060] Example 6
[0061] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 9% hydrophilic fumed nano-silica, 0.6% azobisisobutyronitrile, 8% aminopropyltrimethoxysilane, 0.4% dibutyltin dilaurate, 8% n-dodecyltrimethoxysilane, 18% anhydrous ethanol, 22% deionized water, 16% acid solution, and 18% alkaline solution.
[0062] The performance test process is the same as that of Example 1, but the amount of the hydrophobic material added is 0.8% of the cement content.
[0063] Example 7
[0064] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 7% hydrophilic fumed nano-silica, 0.8% azobisisobutyronitrile, 8% aminopropyltrimethoxysilane, 0.2% dibutyltin dilaurate, 10% n-dodecyltrimethoxysilane, 17% anhydrous ethanol, 22% deionized water, 17% acid solution, and 18% alkaline solution.
[0065] The performance test process is the same as that of Example 1, but the amount of the hydrophobic material added is 1.0% of the cement content.
[0066] Example 8
[0067] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 8% hydrophilic fumed nano-silica, 0.5% azobisisobutyronitrile, 10% aminopropyltrimethoxysilane, 0.5% dibutyltin dilaurate, 11% n-dodecyltrimethoxysilane, 15% anhydrous ethanol, 23% deionized water, 16% acid solution, and 16% alkaline solution.
[0068] The performance test process is the same as that of Example 1, but the amount of the hydrophobic material added is 1.0% of the cement content.
[0069] Example 9
[0070] The difference from Example 1 is that the raw materials used in this example are composed of the following raw materials in weight percentage: 9% hydrophilic fumed nano-silica, 0.6% azobisisobutyronitrile, 8% aminopropyltrimethoxysilane, 0.4% dibutyltin dilaurate, 8% n-dodecyltrimethoxysilane, 18% anhydrous ethanol, 22% deionized water, 16% acid solution, and 18% alkaline solution.
[0071] The performance test process is the same as that of Example 1, but the amount of the hydrophobic material added is 1.0% of the cement content.
[0072] Comparative Example 1
[0073] This comparative example and Example 1 both provide ordinary concrete with the same mix ratio, and the component contents of the raw materials are proportionally increased according to the mix ratio relationship in Example 1, so that the sum of the weight portions of the raw materials is 100%. At the same time, the dosage of each component of the concrete in this comparative example and the performance test process are the same as those in Example 1.
[0074] Comparative Example 2
[0075] This comparative example is different from Example 1 in that only a commonly used hydrophobically modified polymer is added in this comparative example, and the content of other raw materials is expanded in the same proportion according to the ratio relationship in Example 1, so that the sum of the weight parts of the raw materials is 100%.
[0076] According to the performance of Examples 1-9 and Comparative Examples 1-2 provided above in concrete, the obtained results are shown in Table 1.
[0077] Table 1 Test results
[0078] ;
[0079] With reference to the test results provided in Table 1, it can be seen from Examples 1 to 9 that the material for unidirectionally regulating the hydrophilic to hydrophobic conversion of concrete based on pH value provided by the present invention can ensure the strength of concrete while enhancing the hydrophobicity of concrete. By comparing Examples 1 to 9, it can be seen that the material provided by the present invention is added to concrete, not only the strength of concrete is improved, but also the water absorption rate of the entire concrete is reduced, and the SA contact angle is increased. At the same time, it can be seen from Examples 1 to 6 that with the increase in the amount of hydrophobic material, the compressive strength of concrete shows a trend of first increasing and then decreasing, which shows that the material provided by the present invention can make concrete more compact and increase its strength within a certain range, but the excessive amount will cause the strength of concrete to decrease. And it can also be concluded from Examples 1 to 9 that the amount of hydrophobic material increases, the water absorption rate of concrete gradually decreases, and the contact angle gradually increases, which shows that a significant hydrophobic effect is shown in the late stage of concrete hardening, and the durability of concrete is improved.
[0080] By comparing Example 5 and Example 6 with Comparative Example 1 and Comparative Example 2, the present invention significantly improves the contact angle between the concrete surface and the water droplet, which can reach up to 130°, and the water absorption rate is reduced to 87.03%, which can effectively prevent the intrusion of external moisture and show excellent hydrophobic performance. At the same time, the compressive strength of the concrete increased by 18% after curing for 28 days, which shows that the material provided by the present invention improves its hydrophobicity while ensuring the strength of the concrete.
[0081] In summary, the present invention improves the hydrophobic effect of concrete while ensuring the strength of concrete. Compared with Comparative Example 2, the concrete mixed with the hydrophobic material proposed by the present invention has a strength increase of 11%, a water absorption decrease of 41.82%, and a contact angle increase of 32.97% after 28 days. This shows that the material increases the impermeability and durability of concrete while improving the strength of concrete.
[0082] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0083] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A material for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value, characterized in that: The invention is composed of the following raw materials by weight percentage: 7% to 12% inorganic filler, 0.40% to 1.20% azobisisobutyronitrile, 5% to 10% aminopropyltrimethoxysilane, 0.20% to 1.00% dibutyltin dilaurate, 7% to 11% hydrophobic modifier, 14% to 19% anhydrous ethanol, 14% to 20% acid solution, 13% to 18% alkaline solution, and 20% to 24% deionized water; the inorganic filler is selected from hydrophilic gas-phase nano-silica or inorganic particle material, wherein the inorganic particle material is composed of one of nano-scale or micron-scale diatomaceous earth, zinc oxide, nano-titanium dioxide, nano-clay, carbon-based nano-material or solid waste inorganic material; the hydrophobic modifier is selected from one of n-dodecyltrimethoxysilane or long-carbon-chain hexadecyltrimethoxysilane and n-octadecyltriethoxysilane.
2. The method for preparing a material for unidirectionally regulating the conversion of concrete hydrophilic to hydrophobic based on pH value according to claim 1, characterized in that: The following steps are involved: Step S1, weighing hydrophilic fumed nano-silica, aminopropyltrimethoxysilane and n-dodecyltrimethoxysilane according to the weight percentage of the raw materials for later use; Step S2, adding aminopropyltrimethoxysilane into a beaker containing anhydrous ethanol, and heating in a water bath to obtain a composite solution A; Step S3, under the same reaction conditions as step S2, adding hydrophilic fumed nano-silica to the composite solution A, adding azobisisobutyronitrile, continuing to stir to obtain a suspension solution B, filtering through a nanofiltration membrane to obtain a nano-silica wet body C, and washing, drying, grinding, and sieving to obtain a nano-silica powder D; Step S4, adding n-dodecyltrimethoxysilane to another beaker containing anhydrous ethanol, heating in a water bath, and stirring to obtain a composite solution E; Step S5, under the same reaction conditions as step S4, dibutyltin dilaurate and the obtained nano-silica powder D are added to the composite solution E, and the suspension solution F is obtained by continuous stirring, and the suspension solution F is filtered through a nanofiltration membrane to obtain a nano-silica wet body G, and the nano-silica powder H is obtained by washing, drying, grinding, and sieving; Step S6, adding the obtained nano-silicon dioxide powder H into a beaker containing an acid solution, stirring and filtering, washing and drying, grinding and sieving at room temperature, to obtain a material for unidirectionally regulating the conversion of concrete from hydrophilic to hydrophobic based on pH value.
3. The method for preparing a material for unidirectionally regulating the conversion of concrete hydrophilic to hydrophobic based on pH value according to claim 2, characterized in that: In step S3, the preparation process of nano-silica powder D is as follows: the obtained nano-silica wet body C is washed alternately with anhydrous ethanol and deionized water three times, and stored at room temperature for 2 hours, and then placed in a drying oven at 80°C for 8 hours. After drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain nano-silica powder D.
4. The method for preparing a material for unidirectionally regulating the conversion of concrete hydrophilic to hydrophobic based on pH value according to claim 2, characterized in that: In step S4, the preparation process of composite solution E is as follows: heating a beaker containing anhydrous ethanol and n-dodecyltrimethoxysilane in a water bath at a temperature of 50°C to 60°C, and stirring at a speed range of 500r / min to 800r / min to obtain composite solution E.
5. The method for preparing a material for unidirectionally regulating the conversion of concrete hydrophilic to hydrophobic based on pH value according to claim 2, characterized in that: In step S5, the preparation process of the nano-silica powder H is as follows: the obtained nano-silica wet body G is washed twice with anhydrous ethanol and deionized water alternately, and stored at room temperature for 2 hours, and then placed in a drying oven at 80°C for 8 hours. After drying, it is cooled and ground, and passed through an 800-mesh sieve to obtain the nano-silica powder H.
6. The method for preparing a material for unidirectionally regulating the conversion of concrete hydrophilic to hydrophobic based on pH value according to claim 2, characterized in that: In step S6, the preparation process of the material for unidirectionally regulating the conversion of hydrophilic to hydrophobic concrete based on pH value is as follows: placing the obtained nano-silica powder H in a beaker filled with an acid solution, stirring for 1 minute at room temperature and filtering, then washing twice with anhydrous ethanol and deionized water alternately, and then placing it in a drying oven at 80°C for drying for 3 hours. After drying, cooling and grinding are performed, and passing through an 800-mesh sieve to obtain the material for unidirectionally regulating the conversion of hydrophilic to hydrophobic concrete based on pH value, and then treating it with an alkaline solution before adding it to concrete.
Citation Information
Patent Citations
Super-hydrophobic water-based emulsion for cement-based material as well as preparation method and application of super-hydrophobic water-based emulsion
CN113880494A
Waste residue-based hydrophobic high-performance concrete admixture as well as preparation method and application thereof
CN116040982A